2019
DOI: 10.31557/apjcp.2019.20.2.391
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reflexology on Fatigue Severity of Patients with Cancer

Abstract: Introduction:Breast cancer is a major threat to women’s health and a common factor that can reduce their life expectancy. Complementary medicine such as reflexology is known to reduce fatigue severity in cancer patients. The present study aimed to cultivate the effect of reflexology on fatigue severity of patients with breast cancer. Methods:The present pre-post clinical trial recruited 57 patients with breast cancer and involved an experimental and a control group. All patients were livening in Ilam, Iran. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 21 publications
0
24
0
9
Order By: Relevance
“…Regarding the fatigue assessment tools, three studies [ 26 , 27 , 31 ] used the Brief Fatigue Inventory (BFI), and two studies [ 23 , 24 ] adopted the Berlin Mood Questionnaire (BSF; fatigue subscale) for fatigue assessment. One each study employed the Fatigue Severity Scale (FSS) [ 33 ], the Chronic Fatigue Syndrome (CFS) Score [ 29 ], the MD Anderson Symptom Inventory [ 32 ], and the Profile of Mood States (POMS) Questionnaire (fatigue subscale) [ 22 ]. Noteworthily, Kinkead et al [ 25 ] used the Multidimensional Fatigue Inventory (MFI) and the PROMIS Fatigue Short Form 7a (PROMIS) to evaluate fatigue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the fatigue assessment tools, three studies [ 26 , 27 , 31 ] used the Brief Fatigue Inventory (BFI), and two studies [ 23 , 24 ] adopted the Berlin Mood Questionnaire (BSF; fatigue subscale) for fatigue assessment. One each study employed the Fatigue Severity Scale (FSS) [ 33 ], the Chronic Fatigue Syndrome (CFS) Score [ 29 ], the MD Anderson Symptom Inventory [ 32 ], and the Profile of Mood States (POMS) Questionnaire (fatigue subscale) [ 22 ]. Noteworthily, Kinkead et al [ 25 ] used the Multidimensional Fatigue Inventory (MFI) and the PROMIS Fatigue Short Form 7a (PROMIS) to evaluate fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the massage protocols used in the included studies are shown in Table 3 , including massage modalities, procedures, intervention instructors, timing of the interventions, and duration/frequency of the interventions. Four massage therapy modalities were identified in the review, of which reflexology therapy was adopted by four studies [ 27 , 31 33 ], Swedish massage therapy was adopted by four studies [ 23 26 ], and Chinese massage therapy [ 29 ] and myofascial therapy [ 24 ] were adopted by one each study. Of the four studies that used reflexology therapy, one each was performed by a trained researcher [ 27 ], a trained caregiver [ 32 ], and certified reflexologists [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, American ginseng appears not to inhibit the cytochrome p450 system 28 and has not been found to impact the effects of tamoxifen, doxorubicin, cyclophosphamide, paclitaxel, 5-fluorouracil, and methotrexate, but was instead synergistic with these agents inhibiting growth in MCF-7 breast cancer cell lines. 29,30 Effectiveness Not Established or Effectiveness Unlikely-Numerous treatments, detailed in Figure 3, have insufficient evidence to recommend them for clinical practice in cancer patients during active treatments (Effectiveness Not Established) including Asian ginseng (Panex ginseng), 31 guarana, 32 and Inner power 33 (an amino acid, coenzyme Q10, Lcarnitine blend); and music therapy, 34 progressive muscle relaxation, [35][36][37] qigong, 38 reflexology, 39 tai chi 40,41 and yoga, 42,43 and laser moxibustion. 44 Also, detailed in Figure 2 are 2 supplements, coenzyme Q10 45 and L-carnitine 46 that have research that indicates they are likely ineffective for treating CRF during active cancer treatment (Effectiveness Unlikely).…”
Section: Overview Of Interventions For Crf During Active Treatmentmentioning
confidence: 99%
“…51 As with any physical activity, however, sprains and strains are possible, especially to the knee, and this should be taken into account when recommending this therapy. 52 Effectiveness Not Established-Many treatments, detailed in Figure 4, have insufficient evidence to recommend them for clinical practice in posttreatment cancer survivors (Effectiveness Not Established) including the herbal supplements PG2 (Astragalus membranaceus) 53 and American ginseng, 15,27 and acupuncture, 54,55 biofield energy, 56 massage therapy, 57 laser moxibustion, 44 progressive muscle relaxation (PMR), 35 reflexology, 39 mindfulness-based stress reduction (MBSR), 58 and a multimodal mind-body medicine, nutrition, and exercise treatment. 59…”
Section: Overview Of Interventions For Crf Posttreatmentmentioning
confidence: 99%